The Exception that Proves the Rule? Schengen and the Reintroduction of Internal Border Controls - Gyeney Laura (HUNGARIAN YEARBOOK OF INTERNATIONAL LAW AND EUROPEAN LAW, 2024)
The Schengen area is a cornerstone of European integration. In recent years, however, the integrity of the Schengen area has been tested by the migration crisis, terrorism, and, not least, the COVID-19 pandemic. Some Member States have responded to these crises by maintaining border controls beyond the six-month time limit set by the Schengen Borders Code. This study aims to examine whether Member States can invoke public security considerations to reintroduce border controls for a more extended period and whether integration requirements of free movement can be balanced against the security interests of Member States in the Schengen area.